2016
DOI: 10.3389/fpls.2016.01276
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Bread Wheat Genotypes for Drought Tolerance Using Phenotypic and Proline Analyses

Abstract: Drought stress is one of the leading constraints to wheat (Triticum aestivum L.) production globally. Breeding for drought tolerance using novel genetic resources is an important mitigation strategy. This study aimed to determine the level of drought tolerance among diverse bread wheat genotypes using agronomic traits and proline analyses and to establish correlation of proline content and agronomic traits under drought-stress conditions in order to select promising wheat lines for breeding. Ninety-six diverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
158
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 222 publications
(182 citation statements)
references
References 36 publications
23
158
1
Order By: Relevance
“…Previous studies identified some of the major QTL encoding for functional genes that control most agronomic traits in wheat under drought-stressed conditions (Spielmeyer et al, 2007;Mathews et al, 2008;Li et al, 2015;Mwadzingeni et al, 2016a). Some of the genetic components affecting plant height could also influence spike length since the two traits are highly correlated, and both have high heritability estimates (Mwadzingeni et al, 2016b). Owing to the high heritability estimates observed in this study, association mapping based on the studied set of germplasm and traits could probably identify genetic determinants influencing these traits under contrasting environments.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Previous studies identified some of the major QTL encoding for functional genes that control most agronomic traits in wheat under drought-stressed conditions (Spielmeyer et al, 2007;Mathews et al, 2008;Li et al, 2015;Mwadzingeni et al, 2016a). Some of the genetic components affecting plant height could also influence spike length since the two traits are highly correlated, and both have high heritability estimates (Mwadzingeni et al, 2016b). Owing to the high heritability estimates observed in this study, association mapping based on the studied set of germplasm and traits could probably identify genetic determinants influencing these traits under contrasting environments.…”
Section: Discussionmentioning
confidence: 87%
“…This study partitioned variance components and estimated their influence on heritability values of yield and yield related traits in a set of candidate wheat germplasm. The lines were selected from CIMMYT pre-breeding nurseries for drought and heat tolerance and found to be useful for drought tolerance breeding (Mwadzingeni et al, 2016b). The significant genotypic differences (P < 0.001) observed for the studied traits reflects that the germplasm pool from which the sampled lines were selected contains a broad genetic base (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, a simultaneous increase (or decrease) in T 2 and LWW for a specific water compartment is strong evidence for a change in water content in the cell compartment without taking other mechanisms such as solute concentration or membrane permeability, into account. All of these mechanisms can be affected by water stress, a reduction in the water in the leaf and hence in the vacuoles is a known effect of water stress [25] as is an increase in the concentration of soluble compounds [53]. Moreover, the permeability of the tonoplast increases [54,55] or decreases [56,57] depending on the stress and the species.…”
Section: Impact Of Mild Drought Stressmentioning
confidence: 99%